Balinese Nurses and the Multifaceted Role Burden: A Qualitative Exploration - Ni Luh Putu Dian Yunita Sari; Luh Putu Widiastini; I Putu Artha Wijaya (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Female nurses in Bali face several challenges after marriage, including cultural expectations, domestic responsibilities, and professional demands in the workplace. This may be a risk factor for physical and psychological problems. This study aimed to determine the perspectives of female Balinese nurses on their triple roles, so it contribute to existing literature on gender roles and nursing in patriarchal. Methods: This study uses a qualitative methodology underpinned by a phenomenological framework. Data were obtained through in-depth interviews and subjected to a systematic analysis involving transcription, thematic categorization, and processing using N-Vivo 12 software. The population in this study consisted of Balinese Hindu women who worked as nurses. Participants were determined using a purposive sampling technique with the following inclusion criteria: willing to be a participant, able to speak Indonesian, a nurse, as a housewife and already having children, working with a shift system or clearly scheduled (at least 40 hours/week), and active in traditional activities. The exclusion criterion was Balinese women with cognitive, mental, and verbal communication disorders. Twelve participants were interviewed until data saturation was reached. This study was approved by the Health Research Ethics Committee of Stikes Bina Usada Bali (Approval Number: 082/EA/KEPK-BUB-2025). All participants provided informed consent before participating in the study. Results: This research resulted in 6 themes, namely adaptation process, challenges as a Balinese' woman, perceived complaints, strategies to balance roles as Balinese women, support received, and feeling as a Balinese' woman. Participants explained their perspectives and experiences in balancing roles at home, as workers, and as part of Balinese society. Their multiple roles have led to physical and psychological complaints. However, some participants also revealed that there is support from the environment and positive affirmation that being a married Balinese woman is pride, because it is strong and awesome. Conclusion: This study uncovered six themes that deeply describe what Balinese female nurses experience and feel. These results are expected to help community nurses take strategic steps in providing nursing care to a special aggregate, namely, working women in the Balinese community.